(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Being the son of a Sunni father and Shia mother, Akbar got a liberal family environment right from the beginning. When he took hold of his kingdom at the age of thirteen, he wanted to establish a strong kingdom as a ruler. Keeping in his mind the historical background of his predecessors, a proper religious policy was required to follow. After going through different aspects of religion in the world, Akbar concluded with the fact that all religions preach the same idea. That is why, he wanted to establish a religion which favours people belonging to all religion. Because of his outlook and attitude towards religion, Akbar holds a distinctive place in the history of Mughal rulers.